Molecular cloning and characterization of partial cDNA encoding for flavanone 3-hydroxylase from kelampayan (neolamarckia cadamba) - Low, Hui Chia (Universiti Malaysia Sarawak, UNIMAS, 2013)
Neolamarckia cadamba or Kelampayan is a type of deciduous tree species classified under the Rubiaceae family. The fast fast-growing N. cadamba emerges as a new alternative to meet high global demand of timber wood. Flavanone 3-hydroxylase is one of the key enzymes involved in the flavonoid synthesis pathway. Thus, this study aims to amplify the flavanone 3-hydroxylase partial cDNA in order characterize it through sequence analysis. High quality total RNA was extracted from the young leaves of N. cadamba and converted into cDNA. Amplification of cDNA encoding flavanone 3- hydroxylase was performed through PCR. The BLASTn result of purified PCR product revealed high similarity with the flavanone 3-hydroxylase (F3H) mRNA of other plant species, comfirming the identity of the nucleotide sequence as the partial cDNA of flavanone 3-hydroxylase.